Transmission of Streptococcus mutans in some selected families - Masuda, N; Shimamoto, T; Kitamura, K; Sobue, S; Hamada, S (Microbios, 1985)
The aim of the present study was to determine the source and transmission route of Streptococcus mutans. The frequency of this organism in saliva and plaque samples was compared among fifteen pairs of mothers and their children. The results showed that most of the mothers harboured almost equal or greater levels of S. mutans than their children. Similarities of the distribution of various serotypes and mutacin types were observed between these mothers and their offspring. Samples were also collected from plaque and/or carious lesions of the relatives of the subjects who carried one of the serotypes other than serotype c as the dominant S. mutans. The strains of the same serotypes of S. mutans which possessed similar mutacin patterns were predominantly detected in the siblings and mothers of each subject. However, a similar distribution of S. mutans strains was not clearly observed in other relatives including fathers, aunts, uncles and grandparents.